2016
DOI: 10.1245/s10434-016-5121-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Postoperative Morbidity and Receipt of Adjuvant Therapy on Long-Term Survival After Resection for Gastric Adenocarcinoma: Results From the U.S. Gastric Cancer Collaborative

Abstract: Postoperative complications adversely affect long-term outcomes after gastrectomy for gastric cancer. Not receiving adjuvant therapy in the face of POC portends an especially poor prognosis following gastrectomy for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 29 publications
3
55
1
Order By: Relevance
“…Our group previously identified independent associations between post-operative complications and decreased OS following resection of various tumors including ACC and gastric carcinoma [15,20]. Peritoneal carcinomatosis and laparoscopy have been anecdotally correlated, however our data do not reflect a difference in tumor recurrence between approaches.…”
Section: Discussioncontrasting
confidence: 51%
“…Our group previously identified independent associations between post-operative complications and decreased OS following resection of various tumors including ACC and gastric carcinoma [15,20]. Peritoneal carcinomatosis and laparoscopy have been anecdotally correlated, however our data do not reflect a difference in tumor recurrence between approaches.…”
Section: Discussioncontrasting
confidence: 51%
“…There has been increased interest in the impact of postoperative complications on long‐term oncological outcomes among patients undergoing surgery for a malignant indication . In fact, the negative impact of postoperative complications on survival after cancer surgery has been investigated across several solid tumor types including esophageal, adrenocortical, colorectal, and gastric malignancies . Previous investigators have suggested that activation of inflammatory mediators associated with postoperative complications around the time of surgery can adversely impact long‐term patient outcomes by modulating the immune response to cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis for patients with gastric cancer treated in the United States is improving, the lack of long‐term satisfactory survival—even after maximal surgical management, low rates of receipt of adjuvant therapy, and delays in receipt of adjuvant therapy—have prompted investigations into the utility of preoperative therapy. On the basis of multiple clinical trials in gastric cancer, preoperative therapy is an accepted treatment approach for patients with resectable ≥T2 disease and any node‐positive disease .…”
Section: Introductionmentioning
confidence: 99%